Severe mitral stenosis with giant LA with LA thrombus - A case report - Hoque, Asraful; Moinuddin, Shahriar; Hossain, Md Monzur; Ahmed, Ahsanara Binte; Nazmi, Ashfaq; Sultana, Souda; Khan, Musfeq Us Saleheen; Hosaain, Md Tanvir (Bangladesh Heart Journal, 2018)
Excess dilatation of the left atrium >60 mm is known in the literature as a gigantic atrium. This dilation is most commonly encountered in the mitral insufficiency of rheumatic etiology, but also in severe prolapses of the mitral valve, permanent atrial fibrillation, and at the leftright shunt with cardiac insufficiency. In this paper, we presented a case study of severe mitral stenosis with giant LA with LA thrombus in a 42 years old female patient. The patient underwent successful mitral valve replacement and removal of LA thrombus and discharged from the hospital with advice. Bangladesh Heart Journal 2018; 33(2) : 141-144